Role of Yogic Procedures in Diabetes and Cardiovascular Diseases - Sharma, Neetu; ram, Sukha (International Research Journal of Ayurveda & Yoga, 2021)
Introduction: Yoga is an ancient Indian way of life and it includes changes in mental attitude, diet, practice of specific technique such as Yogasana, Pranayama and meditation to attain the highest level of consciousness. Yogic procedures are very helpful to manage diabetes and cardiovascular diseases. Methods: The information has been collected from many research articles which are available on authentic research journals and Ayurveda classical texts. Conclusion: Yogic postures stimulates the pancreas, increasing the blood and oxygen supply that works on pancreatic cells and rejuvenate the beta cells which are responsible for reducing blood sugar level in diabetic patients. Pranayama and meditation techniques are beneficial to decrease physiological manifestation of stress by reducing heart rate, blood pressure. Thus, yogic procedures have important role to manage diabetes and cardiovascular diseases.